Mycoplasma pneumoniae infection presenting as stroke and meningoencephalitis with aortic and subclavian aneurysms without pulmonary involvement - Sarathchandran, Pournamy (BMJ Case Rep, 2018)
A 39-year-old Philipino man presented with acute onset fever and headache. Neurological examination was normal except for neck stiffness. There was no history of chest pain, cough or breathlessness. Cerebrospinal fluid (CSF) showed a mild increase in protein with normal sugar and lymphocytic pleocytosis. CSF PCR for herpes simplex and varicella zoster virus was negative. He developed acute right haemiplegia a week after hospitalisation. MRI showed acute infarct in the left centrum semiovale. His angiogram showed aneurysm in the left subclavian artery and aortic arch. The mycoplasma antibody test came positive with very high titres, while rest of the workup was negative. He was treated with azithromycin and his symptoms improved completely. He was asymptomatic on follow-up after a month. His repeat immunoglobulin G mycoplasma antibody titre showed elevation. Mycoplasma infection is a treatable cause of meningoencephalitis and stroke secondary to vasculitis. Arterial aneurysms are known to occur with mycoplasma infection although rare.